Limited neuropeptide Y precursor processing in unfavourable metastatic neuroblastoma tumours - Bjellerup, P (Nature Publishing Group, 2000)
Neuropeptide Y (NPY) is found at high concentrations in neural crest-derived tumours and has been implicated as a regulatory peptide in tumour growth and differentiation. Neuroblastomas, ganglioneuromas and phaeochromocytomas with significant concentrations of NPY-like immunoreactivity were investigated for different molecular forms of NPY and for significance of proNPY processing. Gel-permeation chromatography identified intact NPY (1–36) in all tumours, whereas proNPY (69 amino acids) was detected only in control adrenal tissue and malignant neuroblastomas. Purification of NPY-like immunoreactivity in tumour extracts and structural characterization revealed that both NPY (1–36) and the truncated form NPY (3–36) was present. The degree of processing of proNPY to NPY in tumour tissue was lower in advanced neuroblastomas with regional or metastatic spread (stage 3 and 4) (n = 6), (41%, 12–100%, median, range), compared to the less aggressive stage 1, 2 and 4S tumours (n = 12), (93%; 69–100%), (P = 0.012). ProNPY processing of less than 50% was correlated with poor clinical outcome (P = 0.004). MYCN oncogene amplification was also correlated to a low degree of proNPY processing (P = 0.025). In summary, a low degree of proNPY processing was correlated to clinical advanced stage and poor outcome in neuroblastomas. ProNPY/NPY processing generated molecular forms of NPY with known differences in NPY-receptor selectivity, implicating a potential for in vivo modulation of NPY-like effects in tumour tissue. © 2000 Cancer Research Campaign